PENGARUH DIPLOMASI HALLYU MELALUI FENOMENA BTS TERHADAP FANDOM KOREA DI JAKARTA TAHUN 2013-2023 - Pertiwi, Setya Ambar; Tipa, Aaron Arveno (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Globalization has opened up opportunities for various countries to promote their culture throughout the world, including South Korea with the Hallyu or Korean Wave phenomenon through cultural diplomacy. South Korea's cultural diplomacy is one of its soft power strategies to improve the country's image in the world. One important instrument of Hallyu is the boy band BTS, which has achieved global popularity and plays a significant role in South Korea's cultural diplomacy. This research aims to find out how Hallyu diplomacy influences the Korean fandom through the BTS phenomenon in Jakarta. This research uses mixed methods with data collection techniques using questionnaires, interviews and literature review. The results of this research show that cultural diplomacy through the Hallyu phenomenon, especially through BTS, has had a significant impact on the Korean fandom in Jakarta and the two have a positive correlational relationship of 35.7%, which means there are 64.3% other factors that will influence the Korean fandom's lifestyle which are not examined in this research. This impact also strengthens South Korea's positive image in the eyes of the Indonesian people, especially its fans.